Automated generation of flat tileable patterns and 3D reduced model simulation. (August 2022) - Manolas, Iason; Laccone, Francesco; Cherchi, Gianmarco; Malomo, Luigi; Cignoni, Paolo
Abstract: The computational fabrication community is developing an increasing interest in the use of patterned surfaces, which can be designed to show ornamental and unconventional aesthetics or to perform as a proper structural material with a wide range of features. Geometrically designing and controlling the deformation capabilities of these patterns in response to external stimuli is a complex task due to the large number of variables involved. This paper introduces a method for generating sets of tileable and exchangeable flat patterns as well as a model-reduction strategy that enables their mechanical simulation at interactive rates. This method is included in a design pipeline that aims to turn any general flat surface into a pattern tessellation, which is able to deform under a given loading scenario. To validate our approach, we apply it to different contexts, including real-scale 3D printed specimens, for which we compare our results with the ones provided by a ground-truth solver. Graphical abstract: Highlights: Patterns are interesting from a visual and a mechanical perspective. Their computational design is complex and an intriguing task. We provide an efficient simulation model with our generated flat patterns. Pipeline for direct design of tiled patterns' assemblies. Design exploration with an interactive tool that manages geometry and loads.